2009
DOI: 10.1186/1471-2334-9-167
|View full text |Cite
|
Sign up to set email alerts
|

Identification and genotyping of bacteria from paired vaginal and rectal samples from pregnant women indicates similarity between vaginal and rectal microflora

Abstract: BackgroundThe vaginal microflora is important for maintaining vaginal health and preventing infections of the reproductive tract. The rectum has been suggested as the major source for the colonisation of the vaginal econiche.MethodsTo establish whether the rectum can serve as a possible bacterial reservoir for colonisation of the vaginal econiche, we cultured vaginal and rectal specimens from pregnant women at 35-37 weeks of gestation, identified the isolates to the species level with tRNA intergenic length po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 47 publications
(76 reference statements)
6
73
1
1
Order By: Relevance
“…L. vaginalis belonging to the L. reuteri subgroup which has been reported to be detected in the human vaginal tract (Fredricks et al, 2005;Verhelst et al, 2004), was also detected in 50% of the subjects. Although, Lactobacillus species such as Lactobacillus casei, Lactobacillus delbrueckii, Lactobacillus fermentum, Lactobacillus oris, L. reuteri, Lactobacillus rhamnosus, Lactobacillus helveticus and Lactobacillus salivarius have been reported to be detected as the minor populations in the vaginas of healthy or BV subjects (El Aila et al, 2009;Verhelst et al, 2005;Zhou et al, 2007), such species were not detected in any subjects tested in this study. All of these species should have been covered by the subgroup/ species primer sets if their amounts exceed the detection limit of RTqPCR, suggesting that Lactobacillus populations in the Japanese subjects might be limited to the simple composition.…”
Section: Discussioncontrasting
confidence: 61%
“…L. vaginalis belonging to the L. reuteri subgroup which has been reported to be detected in the human vaginal tract (Fredricks et al, 2005;Verhelst et al, 2004), was also detected in 50% of the subjects. Although, Lactobacillus species such as Lactobacillus casei, Lactobacillus delbrueckii, Lactobacillus fermentum, Lactobacillus oris, L. reuteri, Lactobacillus rhamnosus, Lactobacillus helveticus and Lactobacillus salivarius have been reported to be detected as the minor populations in the vaginas of healthy or BV subjects (El Aila et al, 2009;Verhelst et al, 2005;Zhou et al, 2007), such species were not detected in any subjects tested in this study. All of these species should have been covered by the subgroup/ species primer sets if their amounts exceed the detection limit of RTqPCR, suggesting that Lactobacillus populations in the Japanese subjects might be limited to the simple composition.…”
Section: Discussioncontrasting
confidence: 61%
“…Fecal samples were shown to harbor only a few clones identified as Actinomyces, with "A. viscosus" and A. odontolyticus being represented (42). Actinomyces species found in the human (female) urogenital tract in the absence of actinomycetal infection include A. meyeri, A. neuii, A. radingae, A. turicensis, and A. urogenitalis (43)(44)(45)(46)(47). After the detection of Actinobaculum schaalii (currently Actinotignum schaalii), a taxon closely related to the members of the genus Actinomyces, in urine, groin swabs, and vaginal swabs (18), it was recently suggested that this organism might be a relatively frequent commensal residing on the skin and mucosae of urogenital sites, but not in the colon, since no detection from feces was made (48).…”
Section: Other Sites Of Bacterial Colonizationmentioning
confidence: 99%
“…Gonococcal strain FA1090 did not utilize iron from salmochelin S4 but did obtain iron from S2. As microbial producers of enterobactin, DHBS and salmochelin inhabit the same niche as the gonococcus (21,55), it seems likely that the ability to hijack these siderophores, in the presence of neutrophil-derived siderocalin, enhances the survival of N. gonorrhoeae in vivo.…”
Section: Discussionmentioning
confidence: 99%